Effect of commodity transaction tax on the intraday liquidity of futures: emerging market scenario - Christina Tensingh, Sharon; Thenmozhi, M (BOHR Journal of Financial Market and Corporate Finance, 2025)
This paper examines intraday liquidity dynamics during the onset of commodity transaction tax (CTT) in the Indian futures market. The data analyzed comprises non-agricultural Indian commodity futures contracts from 2013 to 2014. From the analysis, we observe that changes associated with spread-based liquidity measures in commodity markets are significant post-CTT, but the direction of the impact is mixed. However, there is a distinct decline in market depth post-CTT uniformly across all commodities. Furthermore, a visual examination of the liquidity patterns before and after CTT shows that the “U shape” pattern common to intraday stock spread is absent in the commodity futures market. We conclude that spreads are unable to capture implicit transaction costs in the short term, while depth declines post-CTT, supporting Amihud’s view that tax hinders market participation. Currently, studies examining emerging market liquidity, specifically in the context of intraday futures and taxation, are almost non-existent. Our study suggests policymakers exert caution while measuring the impact of transaction taxes using intraday liquidity measures.